Determinants of Sugar-Sweetened Beverage Consumption Among the Saudi Adults: Findings From a Nationally Representative Survey - Al-Hanawi, Mohammed Khaled; Ahmed, Moin Uddin; Alshareef, Noor; Qattan, Ameerah Mohammad Nour; Pulok, Mohammad Habibullah (Frontiers in Nutrition, 2022)
Background Saudi Arabia is the fifth largest consumer of calories from sugar-sweetened beverages (SSBs) in the world. However, there is a knowledge gap to understand factors that could potentially impact SSB consumption in Saudi Arabia. This study is aimed to examine the determinants of SSBs in Saudi Arabia. Methods The participants of this study were from the Saudi Health Interview Survey (SHIS) of 2013, recruited from all regions of Saudi Arabia. Data of a total of 10,118 survey respondents were utilized in this study who were aged 15 years and older. Our study used two binary outcome variables: weekly SSB consumption (no vs. any amount) and daily SSB consumption (non-daily vs. daily). After adjusting for survey weights, multivariate logistic regression models were applied to assess the association of SSB consumption and study variables. Results About 71% of the respondents consumed SSB at least one time weekly. The higher likelihood of SSB consumption was reported among men, young age group (25–34 years), people with lower income (<3,000 SR), current smokers, frequent fast-food consumers, and individuals watching television for longer hours (≥4 h). Daily vegetable intake reduced the likelihood of SSB consumption by more than one-third. Conclusions Three out of four individuals aged 15 years and over in Saudi Arabia consume SSB at least one time weekly. A better understanding of the relationship between SSB consumption and demographic, socioeconomic, and behavioral factors is necessary for the reduction of SSB consumption. The findings of this study have established essential population-based evidence to inform public health efforts to adopt effective strategies to reduce the consumption of SSB in Saudi Arabia. Interventions directed toward education on the adverse health effect associated with SSB intake are needed.